PENGARUH RASIO LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PERUSAHAAN KOSMETIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 (Studi Pada PT. Mustika Ratu, Tbk Dan PT. Martina Berto, Tbk) - Enti Arnas; Saladin Ghalib; Fitriyadi Fitriyadi (JURNAL BISNIS DAN PEMBANGUNAN, 2020)
The companies performance indicators can be seen from the ratio of liquidity, solvency, working capital turnover and profitability. This study aims to prove the effect of liquidity, solvency and working capital ratios on profitability in companies engaged in the cosmetic industry, PT. Mustika Ratu, Tbk and PT. Martina Berto, Tbk,  a quantitative explanatory causality method. The population is the annual report of the two companies in 10 years, a sample of 3 years of financial statements is in 2015-2017.  This study uses multiple linear analysis techniques with data sources are secondary data. The results obtained in this study are; Liquidity ratio (current ratio) partially has a significant effect on profitability (return on equity), solvency ratio (debt to equity ratio) has a partial effect on return on equity, working capital turnover has a partial effect on return on equity, and simultaneously current ratio , debt to equity ratio and working capital turnover affect return on equity. Keywords: Liquidity, Solvency, Working Capital Turnover, Profitability.